Puppet Art Creation Learning To Find Out the Childrens Interests toward Puppet - Kirana, Vemaska; Eka Nugroho, R Agustinus Arum (BELIA: Early Childhood Education Papers, 2016)
Modernization and globalization can erode the national identity if not addressed wisely, one of the nations identity is culture, while cultural elements that most prominent is arts. Puppet art is original art from Indonesia, but nowadays puppet is only in demand by the elderly person and many young children not familiar with puppets, in fact it is they who will preserve the culture of this nation. Puppet Art Creation Learning is a learning which is expected to increase the childrens interest toward puppet. The Learning is implemented in accordance with the early childhood development. This research is using an experimental method. The study population was all students in Pertiwi Ngargomulyo kindergarten. The sampling technique that used is purposive sample technique. The sample collection at Pertiwi Ngargomulyo kindergarten class B1 and B2 Pertiwi Ngargomulyo kindergarten.It can be seen from the table 4.10 Shows there is an increased mean pretest value that originally 102,50 into 139,97 resulting in increased of the mean posttest amounted to 37,47. After being given a treatment, there is an increase in childrenâs interest, it seems from the mean (average) in the experimental group is 139,9. The t test calculation results obtained  value= 12,863 with sig value (2-tailed) < 0,05 so  is accepted. Based on these descriptions, it can be concluded that the giving of Puppet Art Creation Learning can provide significant improvement to the childrens interests.